A descoberta do homoerotismo emcurtas-metragens brasileiros - Jaider Fernandes Reis (2008)
The study proposed here intends to analyze the picture that the Brazilian movies do of the male homosexual configured in characters in movies. The analysis is focused on the production of fiction short films about the masculine homosexuality, specifically the moment of the discovery of the sexuality. The work used the movie critics and theories of analysis of speech, emphasizing the simultaneous game between the probable and the unlikely, besides some studies on homoerotism. We considered that the selected film confirms the hypothesis that the use of verisimilitude as a cinematographic resource makes possible the recognition of thehomoerotic character as an ordinary being, not the crystallization of a stereotype.